2009
DOI: 10.1007/s12272-009-1605-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive triterpenoids from Callistemon lanceolatus

Abstract: A new triterpenoid, 30-hydroxyalphitolic acid 1, and eight known triterpenoids, alphitolic acid 2, lupenol 3, 3-acetoxy-olean-18-en-28-oic acid 4, betulinic acid 5, ursolic acid 6, betulinic acid 3-O-caffeate 7, morolic acid 3-O-caffeate 8, and ursolic acid 3-O-caffeate 9, were isolated from Callistemon lanceolatus. Their structures were determined using spectroscopic techniques, which included 1D- and 2D-NMR. All compounds were evaluated for the inhibition of LPS-induced nitric oxide production in murine macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…The essential oils from leaves possess antimicrobial, fungitoxic, antinociceptive and anti-inflammatory activities. Several triterpenoids, flavonoides, fatty acids, tannins and phenolic compounds have been isolated from its leaves (Sudhakar et al, 2004;Jeong et al, 2009). The leaves was also reported for its hepatoprotective effect (Jain et al, 2007), antidiabetic, hypolipidemic and anti-oxidant activity (Kumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils from leaves possess antimicrobial, fungitoxic, antinociceptive and anti-inflammatory activities. Several triterpenoids, flavonoides, fatty acids, tannins and phenolic compounds have been isolated from its leaves (Sudhakar et al, 2004;Jeong et al, 2009). The leaves was also reported for its hepatoprotective effect (Jain et al, 2007), antidiabetic, hypolipidemic and anti-oxidant activity (Kumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[41] This plant is known for several medicinal properties, viz., anti-inflammatory properties [42] and inhibition of anticholinesterase activity. [43] It is known to contain several volatile oils, [44] polyphenols [41,45] and triterpenoids [46,47] which might be responsible for its medicinal properties. Hence, in this study, we have demonstrated the biological synthesis of silver oxide nanoparticles using the aqueous extract of C. lanceolatus and reported their significant antioxidant and cytotoxic activity.…”
mentioning
confidence: 99%
“…Species Callistemon citrinus (Curtis) Skeels, local name "Tram bong do", is grown as ornaments in Vietnam for its beautiful form, glossy green foliage and red, bottle-brush like flowers. Phytochemical studies of Callistemon species have led to the isolation and characterization of flavones [2], acylphloroglucinols [3,4], triterpenoids [5], neolignans [6], essential oil, steroids and saponins [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we describe the isolation and structural elucidation of eight phenolic compounds, including two flavones (eucalyptin (1) and 8-demethyleucalyptin (2)), two alcohols (blumenol A (3), tetratriacontan-1-ol (4)), three benzoic acid derivatives (gallic acid (5), methyl gallate (6) and protocatechuic acid (7)), one sterol (β-stigmasterol (8)) along with one sesquiterpene (2,6,10-bisabolatriene (9)). The structures of the natural compounds were identified by spectroscopic evidences including 1D-and 2D-NMR and ESI-MS.…”
Section: Introductionmentioning
confidence: 99%